2002
DOI: 10.1002/pat.274
|View full text |Cite
|
Sign up to set email alerts
|

Gel point prediction of metal‐filled castor oil‐based polyurethanes system

Abstract: Gel Point Prediction of Metal-®lled Polyurethanes / 1057 FIGURE 3. Effect of ®ller on gel time at 30°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…It's supposed that gel time can be used to estimate the proper temperature of synthesis. 3 , and glass powder) systems, they stated that the gel time decreases as the percent filler loading is increased and they attributed it to the increased surface area made available for the curing mass with the progressive addition of the filler which is similar to that reported by Rao and Pourassamy [4]. In the present work, Isothermal system was applied to study the effect of milled fiber glass loading on the gel time individually.…”
Section: Introductionsupporting
confidence: 77%
“…It's supposed that gel time can be used to estimate the proper temperature of synthesis. 3 , and glass powder) systems, they stated that the gel time decreases as the percent filler loading is increased and they attributed it to the increased surface area made available for the curing mass with the progressive addition of the filler which is similar to that reported by Rao and Pourassamy [4]. In the present work, Isothermal system was applied to study the effect of milled fiber glass loading on the gel time individually.…”
Section: Introductionsupporting
confidence: 77%
“…Several studies have been reported in the literature on the gelation time phenomenon of polyurethanes. [15][16][17][18][19] Regarding CO-based thermosets, Srivastava et al (2002) predicted the gel point of metal-filled CO-based polyurethanes. It was found that an increase in the process temperature, hydroxyl content or polyol functionality, or also the decrease of aluminium powder content, decreased the gelation time.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that an increase in the process temperature, hydroxyl content or polyol functionality, or also the decrease of aluminium powder content, decreased the gelation time. [20] On the same scheme, Yeganeh et al (2006) prepared polyhydroxyl compounds (PHC) via transesterification of poly(ethylene terephthalate), poly-(ethylene glycol)s and CO. Measurements showed that, with decreasing PHC hydroxyl content, the crosslink density decreased. As expected, the tensile strength and elongation at break decreased with increasing crosslink density.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Srivastava and co-workers showed gel point prediction of metal-filled castor oil based polyurethanes system. [11] Thames et al examined cationic ultraviolet curable coatings from castor oil glycidyl ether and epoxy Summary: Biobased epoxy materials were prepared from diglycidyl ether of bisphenol A (DGEBA) and epoxidized castor oil (ECO) initiated by a latent thermal catalyst. The physicochemical and mechanical interfacial properties of the DGEBA/ECO blends were investigated.…”
Section: Introductionmentioning
confidence: 99%